Nilai Karakter dalam Lagu “Sangu Batulak” Karya Anang Ardiansyah - Marsha Nur Amalia (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study aims to reveal the character values contained in the lyrics of the song Sangu Batulak by Anang Ardiansyah. This traditional Banjar song not only functions as entertainment, but also as a medium for conveying moral and cultural messages to the community. Using a descriptive qualitative approach, this study analyzed the contents of the song lyrics to identify the character values contained therein. The results of the analysis show that the song Sangu Batulak contains a number of important character values, including religious, responsible, independent, compassionate, family, and sincerity. These values are conveyed through the diction and language style typical of Banjar which is full of meaning, and reflects the culture and outlook on life of its people. Thus, Banjar songs have great potential as a contextual and effective character learn-ing medium in forming individuals who are moral and responsible.